Carabid (Coleoptera) type collection at National Forest Insect Collection (NFIC), Forest Research Institute, Dehradun (India) - Faisal, Mohammad; Singh, Sudhir (Zootaxa, 2014)
Members of family Carabidae (Insecta: Coleoptera) are a dominant group of terrestrial predators. National Forest Insect Collection (NFIC) of Forest Research Institute, Dehradun (India) has a good collection of carabids rich in type material. Here we report the details of the type specimens of 139 species included in 49 genera, 24 tribes and 14 subfamilies. Colour automontaged photographs of each type along with its original labels are also included.